A meta-analysis and test of the overlap between honor concern, right-wing authoritarianism, and social dominance orientation - Olivia K. Nop; Matthew D. Hammond (Current Research in Ecological and Social Psychology)
Honor concern—an ideology describing the importance of maintaining reputation in culturally appropriate ways—are theorized to underlie people’s prejudice and violence. However, the domains of honor concern conceptually overlap with other sources of prejudice: right-wing authoritarianism (RWA) and social dominance orientation (SDO). In Study 1, we tested the statistical overlap between honor concern domains with RWA and SDO using a meta-analysis (k = 16; n = 5053). Results identified group honor concern as the most distinct, sharing only moderate overlap with RWA; masculine and feminine honor concern were strongly positively correlated with RWA. Group honor was not correlated with SDO, while masculine and feminine honor concern were strongly and weakly positively correlated with SDO respectively. However, the original studies did not examine each as distinct predictors of prejudice-related outcomes (e.g., patriotism and trait aggression). In Study 2, data collected from online samples from USA and Italy (n = 298) addressed this gap. Latent variable models indicated that group honor concern positively predicted patriotism and negatively predicted general trait aggression, over and above RWA and SDO. Overall, these studies suggest that group honor concern, RWA, and SDO share conceptual similarities but are distinct. Further research is needed to examine the specific contexts in which group honor concern predicts heightened aggression and prejudice.